A Case for Corporate Communication-Oriented Model in the 21st Century Nigerian Public Sector - Inobemhe, Kelvin (Semantik: Journal of Social, Media, Communication, and Journalism, 2025)
Human society could be chaotic without communication and so every nation desirous of orderliness and tranquility requires effective communication across various sectors including the private and This also buttresses the need for government to provide up-to-date information to its public on core and sundry matters including activities, policies, programmes and plans. Therefore, corporate communication-modeled public sector communication is recommended. This implies that the communication must be in a manner as though it is with customers. This study is about the need for corporate communication in the public sector of Nigeria. Accordingly, the researcher demonstrated that different types of corporate communication ÔÇô such as written, oral and nonverbal can be explored by public institutions to approach members of the public who are desirous of information. It was further established in this study that though not devoid of challenges, corporate communication can be an effective way to engage the public on different aspects of nation building and development. It has been identified as one crucial way to get the people involved in the process of development. The study concluded that there is a strong need for the adoption and application of corporate communication in the public sector of Nigeria as obtained in the private to build trust and cooperation of members of the ┬á